Esophageal atresia with tracheoesophageal fistula: A rare variant and cautionary tale - Nicole A. Wilson (Journal of Pediatric Surgery Case Reports, 2017)
Esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) are relatively common congenital anomalies. Additional variants of these anomalies have been reported, including EA-TEF associated with congenital esophageal stenosis (CES) and a few reports of EA-TEF associated with an esophageal web or membranous diaphragm. We report an extremely rare case of EA with distal TEF associated with both a CES and a separate esophageal web distal to the TEF. EA-TEF with an associated CES and/or mucosal web distal to the TEF presents both a diagnostic and management challenge, as the standard diagnostic/pre-operative work-up may not identify the distal areas of esophageal occlusion. Surgeons should be aware and should maintain a high index of suspicion for these anatomic variants as they can lead to operative complications. Use of a tube to confirm patency of the distal esophageal pouch as a standard technique during EA-TEF repair may help avoid the potential pitfalls associated with failure to recognize these conditions. Keywords: Congenital esophageal stenosis, Esophageal atresia, Esophageal web, Tracheoesophageal fistula